PARASITES, PONDERAL INDEX AND LENGTH-WEIGHT RELATIONSHIP OF BARILIUS BENDELISIS (HAM.) AND PUNTIUS TICTO (HAM.) - Gatrola, Damayanti; Singh, Om Veer; Malhotra, Sandeep K; Nanda, Sunita; Ghildiyal, R P (Indian Journal of Fisheries, 2011)
This investigation includes report on the bionomics of economically important fishes, Barilius benddisis(Ham.) and Puntius liclo (Ham.) from diverse ecological situations. Peak values of Ponderal Index (K)in smaller (